Massimo Faggioli, The Liminal Papacy of Pope Francis: Moving toward Global Catholicity. - Rees, John A. (Journal for the academic study of religion, 2021)
Massimo Faggioli, The Liminal Papacy of Pope Francis: Moving toward Global Catholicity. Maryknoll, NY: Orbis Books, 2020, pp. 205, ISBN-13: 978-1626983687 (pbk). US$27.00.